War without end : the rise of Islamist terrorism and global response - Hiro, Dilip (London ; New York : Routledge, 2002)
After providing a brief history of Islam as a religion and as socio-political ideology, Dilip Hiro outlines the Islamist movements that have thrived in Egypt, Saudi Arabia and Afghanistan and their changing relationship with America
The rise of Islam: Sunnis and Shias -- Orthodox Islam and Sufism -- Islam in modern times -- The Muslim Brotherhood in Egypt and its offshoots -- Saudi Arabia: the oldest fundamentalist state -- Afghanistan: fundamentalism victorious, with American backing -- Bombing of US embassies: a wake-up call -- Eighty minutes that shook the world and global response -- Ongoing war against terror: an uncharted territory
Includes bibliographical references (pages 486-490) and index
Keywords: Islamic fundamentalism -- Middle East -- History -- 20th century; Islam and politics -- Middle East -- History -- 20th century; Terrorism -- Middle East -- History -- 20th century; Terrorism -- Religious aspects -- Islam; Fundamentalisme; Islam; Terrorisme; Middle East -- Politics and government -- 1945-; History